The chain mediating role of parenting stress and child maltreatment in the association between maternal adverse childhood experiences and executive functions in preschool children: a longitudinal study - Jinhong Zha; Ruoyu Li; Haiyan He; Peifei Fang; Rongling Huang; Tian Xing; Yuhui Wan (BMC, 2024)
Abstract Background Previous researches found that maternal adverse childhood experiences not only affect the psychological behavior of preschool children, but also have direct or indirect negative effects on the executive functions and cognition of offspring. And, the possible social psychological mechanism between maternal adverse childhood experiences and preschool children's executive functions is still not clear. Objectives This study mainly tries to understand the association between parenting stress and child maltreatment in maternal adverse childhood experiences and children's executive functions through longitudinal cohort. Participants and setting Participants were 2160 preschool children and their mothers who finally completed baseline and 3 waves of follow-up. Methods Using a cohort study, a baseline survey of junior kindergartens was carried out in June 2021 and followed up every six months, with a total of 3 follow-ups. Results We found that executive functions in preschoolers were significantly positively correlated with maternal adverse childhood experiences, parenting stress, physical assault, psychological aggression, neglect and nonviolent discipline (r = 0.180, 0.386, 0.274, 0.302, 0.189, 0.148, respectively, P < 0.01). Further, parenting stress and child maltreatment showed a chain mediating effect between maternal adverse childhood experiences and executive functions in preschoolers, and the total indirect effects accounted for 70.56%, 78.69%, 65.38%, and 68.07% of the total effect, respectively. Conclusions This study found that maternal adverse childhood experiences have a significant impact on the executive functions of preschool children, and parenting stress and child maltreatment are the mediating factors of their association, revealing the potential mechanism between the two associations from the perspective of social psychology.